Answer:
c=5
Step-by-step explanation:
5s + 3c = 50
s+c=12
5(12-c) + 3c=50
60-5c+3c=50
60-2c=50
-2c=-10
c=5
Answer:
Given the system of equation:
......[1]
......[2]
we can rewrite equation [2] as;
......[3]
Substitute equation [3] into [1] to eliminate x, and solve for y;
![2(8-2y)-4y = -4](https://tex.z-dn.net/?f=2%288-2y%29-4y%20%3D%20-4)
Using distributive property: ![a\cdot (b+c) = a\cdot b+ a\cdot c](https://tex.z-dn.net/?f=a%5Ccdot%20%28b%2Bc%29%20%3D%20a%5Ccdot%20b%2B%20a%5Ccdot%20c)
![16-4y -4y = -4](https://tex.z-dn.net/?f=16-4y%20-4y%20%3D%20-4)
Combine like terms;
16 - 8y = -4
Add 4 to both sides we have;
20 - 8y = 0
Add 8y to both sides we have;
20 = 8y
Divide 8 to both sides we have;
![y = 2.5](https://tex.z-dn.net/?f=y%20%3D%202.5)
Substitute the y-value in [3] we have;
![x = 8-2(2.5)](https://tex.z-dn.net/?f=x%20%3D%208-2%282.5%29)
x = 8 - 5 = 3
Therefore, the expression should be substituted into the first equation is,
and also the value of x = 3 and y = 2.5
we have
![\frac{3}{4} +0.6](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B4%7D%20%2B0.6)
we know that
![\frac{3}{4}=0.75](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B4%7D%3D0.75)
and
![0.75=0.40+0.35](https://tex.z-dn.net/?f=0.75%3D0.40%2B0.35)
substitute in the expression
![0.40+0.35 +0.6](https://tex.z-dn.net/?f=0.40%2B0.35%20%2B0.6)
![(0.40+0.60)+0.35](https://tex.z-dn.net/?f=%280.40%2B0.60%29%2B0.35)
![(1.00)+0.35=1.35](https://tex.z-dn.net/?f=%281.00%29%2B0.35%3D1.35)
therefore
<u>the answer is</u>
![1.35](https://tex.z-dn.net/?f=1.35)
Answer:
3.5m
Step-by-step explanation:
A parallelogram has sides 17.3 m and 43.4 m long.
The height corresponding to the 17.3-m base is 8.7 m.
The area of a parallelogram = base × height
= 8.7m × 17.3m
= 150.51m²
Both parallelograms have the same area
Hence, the height, to the nearest tenth of a meter, corresponding to the 43.4-m base is calculated as:
= 150.51m²/43.4m
= 3.4679723502m
Approximately = 3.5m
Answer:
Step-by-step explanation:
i assume x+y=6(1/2)=\frac{13}{2}
![\frac{5}{8}=\frac{x}{y}=\frac{x}{\frac{13}{2}-x}=\frac{2x}{13-2x}\\65-10x=16x \\26 x=65\\2x=5\\x=\frac{5}{2}\\y=\frac{13}{2}-\frac{5}{2}=\frac{8}{2}=4](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B8%7D%3D%5Cfrac%7Bx%7D%7By%7D%3D%5Cfrac%7Bx%7D%7B%5Cfrac%7B13%7D%7B2%7D-x%7D%3D%5Cfrac%7B2x%7D%7B13-2x%7D%5C%5C65-10x%3D16x%20%5C%5C26%20x%3D65%5C%5C2x%3D5%5C%5Cx%3D%5Cfrac%7B5%7D%7B2%7D%5C%5Cy%3D%5Cfrac%7B13%7D%7B2%7D-%5Cfrac%7B5%7D%7B2%7D%3D%5Cfrac%7B8%7D%7B2%7D%3D4)